A novel screening strategy to identify histone methyltransferase inhibitors reveals a crosstalk between DOT1L and CARM1. Issue 4 (7th March 2022) - Si, Yang; Bon, Corentin; Barbachowska, Magdalena; Cadet-Daniel, Veronique; Jallet, Corinne; Soresinetti, Laura; Boullé, Mikaël; Duchateau, Magalie; Matondo, Mariette; Agou, Fabrice; Halby, Ludovic; Arimondo, Paola B.
Abstract : By a novel screening strategy, we identified Compound 4, a published CARM1 inhibitor, inhibits both histone mark H3R2me2a, regulated also by CARM1, and H3K79me2, regulated only by DOT1L, pointing out a crosstalk between CARM1 and DOT1L. Abstract : Epigenetic regulation is a dynamic and reversible process that controls gene expression. Abnormal function results in human diseases such as cancer, thus the enzymes that establish epigenetic marks, such as histone methyltransferases (HMTs), are potentially therapeutic targets. Noteworthily, HMTs form multiprotein complexes that in concert regulate gene expression. To probe epigenetic protein complexes regulation in cells, we developed a reliable chemical biology high-content imaging strategy to screen compound libraries simultaneously on multiple histone marks inside cells. By this approach, we identified that compound 4, a published CARM1 inhibitor, inhibits both histone mark H3R2me2a, regulated also by CARM1, and H3K79me2, regulated only by DOT1L, pointing out a crosstalk between CARM1 and DOT1L. Based on this interaction, we combined compound 4 and DOT1L inhibitor EPZ-5676 resulting in a stronger inhibition of cell proliferation and increase in apoptosis, indicating that our approach identifies possible effective synergistic drug combinations.